Pengaruh Pembiayaan Ijarah dan Murabahah terhadap Profitabilitas pada Bank Umum Syariah di Indonesia - Awaliah, Sany Putri Rabiul; Kartini, Tina; Noor, Iqbaal (Ikatan Da'i Indonesia, 2024)
This study aims to explain the effect of ijarah financing on profitability at Islamic commercial banks in Indonesia, explain the effect of murabahah financing on profitability at Islamic commercial banks in Indonesia and explain the effect of ijarah and murabahah financing on profitability at Islamic banks in Indonesia. The research method used in this study is a quantitative approach with statistical analysis to test the effect of Ijarah and Murabahah financing on the profitability of Islamic banks in Indonesia. The population used is Islamic banks in Indonesia. The samples used in this study were 8 Islamic Banks in Indonesia using purposive sampling technique. The data collection technique used is literature study. The data analysis technique used is the statistical method of multiple linear regression analysis using SPSS. The results showed that there was a negative and significant influence between Ijarah on return on assets, there was a positive and significant influence between Murabahah on return on assets, there was no influence between Ijarah on return on assets and there was a positive and significant influence between Ijarah and Murabahah on return on assets.